Blue Economy and the Impact of Industrialisation on Sustainable Livelihoods: A Case Study of Fisheries in the North Coastal Region of Java - Wasik, Zainul; Gunawan, Sri; Handriana, Tanti (Journal of Ecohumanism, 2024)
This research explores the impacts of the blue economy and industrialisation on sustainable livelihoods in the coastal areas of the North Coast of Java, with a particular focus on the fisheries sector.The main objective of this research is to analyse how changes in blue economy practices, which include sustainable marine resource management approaches, interact with industrialisation processes and their impact on the survival of local fishing communities.The research method used was qualitative with a case study approach, where data was collected through in-depth interviews with fishermen, government officials, and relevant stakeholders, as well as direct observation in the field. Data analysis was conducted using thematic analysis techniques to identify patterns and significant relationships between the factors involved.The results of this study show that industrialisation in the coastal areas of Java's North Coast has vital and complex impacts on the sustainable livelihoods of local fishing communities. On the one hand, industrialisation provides new economic opportunities, such as jobs in the fishing and manufacturing sectors, which can increase community income. However, on the other hand, negative impacts on the aquatic environment due to industrial activities and overexploitation of natural resources threaten the sustainability of the marine ecosystem, which is the main source of livelihood for fishermen.The managerial implications of these findings emphasise the need to integrate blue economy policies with the maturity of sustainable industrial development planning. Policy development that accommodates the needs of local ecosystems and fishing communities, with a pattern of regulating marine protected zones and supporting the shift to environmentally friendly fisheries practices, is key to ensuring the sustainability of fishers' livelihoods and healthy coastal ecosystems. This research provides important insights for policy makers and practitioners involved in marine fisheries resource management and industry development in coastal areas.